Analysis on passenger flow evolution and service facility configuration for large-scale events in outer suburbs - Qin, Huanmei; Jia, Meiru; qian, Cui; Zhang, Yonghuan (European Journal of Transport and Infrastructure Research, 2024)
As more and more large-scale winter events are held in different areas, a reasonable configuration of service facilities is crucial for ensuring the successful execution of these events. Based on an analysis of the passenger flow for large-scale events in outer suburbs, this study has developed a dynamic evolution model to well simulate passenger arrival distribution among nodes and queue performance over time. Subsequently, an optimization model for service facility configuration based on node linkage is proposed. Using a large-scale winter event as a case study, we conclude that assigning a higher objective weight to spectators’ queuing time cost in the optimization model leads to an increase in the number of configured service facilities among nodes, thereby enhancing service quality. Different facility layouts for security checks and ticket checks have no significant effects on the optimal number of configured service facilities and spectator queuing time costs. However, implementing a remote security check can alleviate passenger congestion at downstream nodes and reduce the overall queuing time cost. The dynamic evolution model and the service facilities configuration model are suitable for coordinating passenger flow under limited-service facility provision along with measures such as adjusting facility layouts and controlling passenger flow. Thus, a good match between passenger flow distribution and facility service capacity can be achieved. The research conclusions can provide a reference for the analysis of passenger flow, service facility configuration, and passenger flow organization for large-scale events held in the outer suburbs.